The role of research and higher education sustainable development in Nigeria (2010)
The paper basically examined the role of research and higher education in sustainable development in Nigeria. Stratified sampling was used to select a federal university and a federal research institute, the productive sector and consumers respectively in Oyo state, Nigeria, from which fifty and twenty-five subjects were used for the study. An instrument designed and validated by the researcher was used to collect the data which were analyzed using both descriptive and inferential statistics. Findings are that education, particularly higher education has a tremendously impacted the Nigerian national development while research findingd are hardly properly disseminated and applied by the productive sector. There is heavy dependence on importation, simply because the government has not created the appropriate enabling environment. It was also discovered that if the education industry in Nigeria were properly funded, greater level of development would have taken place than presently obtained. It was recommended that funds should be made available in the right quantum both to the higher education sector and the research institutes to anable them realize their mandate. The industrial sector of the Nigerian economy should patronize our higher educatinal institutions and research institute for local content and product development and also work together with these bodies to set research agenda for the nation. Finally, it was recommended that government should set a research outcome/output dissemination agency to coordiante dissemination of research findings to the appropraite 'publics'